Rapid development of an evidence- and consensus-based guideline for controlling transmission of SARS-CoV-2 in schools during a public health emergency - A process evaluation - Katharina Wabnitz; Katharina Wabnitz; Mike Rueb; Mike Rueb; Lisa M. Pfadenhauer; Lisa M. Pfadenhauer; Brigitte Strahwald; Brigitte Strahwald; Eva A. Rehfuess; Eva A. Rehfuess (Frontiers Media S.A., 2023)
IntroductionDifferent measures to prevent and control the spread of SARS-CoV-2 have been implemented in German schools. Decisions regarding such measures should be informed by evidence regarding their effectiveness, and their unintended consequences for health and society. A multi-stakeholder panel was convened to develop an evidence- and consensus-based guideline for school measures, using the novel WHO-INTEGRATE framework. Developing a guideline to inform decision-making outside of the clinical realm during a public health emergency was unprecedented in Germany. This study aims to identify lessons learnt for similar endeavours by addressing the following research question: What were the strengths and weaknesses of the guideline development process as perceived by the different groups involved?MethodsFifteen semi-structured interviews were conducted virtually. We recruited participants aiming to include the perspectives of all groups contributing to the guideline development, including both panel members (scientists, practitioners, school family and observers) and the guideline secretariat. For analysis, we carried out deductive-inductive thematic qualitative text analysis according to Kuckartz, structuring findings using a category system.ResultsDue to time pressure, the guideline secretariat was heavily involved not only in synthesising the evidence but also in developing and drafting recommendations. Participants critically reflected on certain methods-related decisions, including the development of draft recommendations and application of the WHO-INTEGRATE framework by scientists only. The full potential of the framework might not have been harnessed. Participants' understanding of relevant and valid evidence varied, and the available evidence base was limited. Participants represented different types of expertise, notably expertise informed by scientific evidence and expertise grounded in lived experience, influencing their involvement in the guideline development process and discussions during meetings.ConclusionDeveloping an evidence- and consensus-based public health guideline in only three months was challenging, notably because of the involvement of a broad range of stakeholders and the use of a novel Evidence-to-Decision framework, both unprecedented in Germany. Learning from this process with a view to "institutionalising" the development of public health guidelines and refining methods can contribute to more evidence-informed public health decision-making in Germany and beyond, in general and during a public health emergency.